POLA REKRUTMEN CALON ANGGOTA LEGISLATIF DPRD KOTA PEKANBARU PERIODE 2019-2024 (STUDI KASUS DPC PARTAI DEMOKRAT KOTA PEKANBARU) - Sandriyani, Septia; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The importance of the role of legislators for the sustainability of democracy in Indonesia makes the recruitment process of these legislators also important because the good or bad of the legislature members who sit in parliament will be determined by the recruitment process. The Pekanbaru City DPRD legislative elections for the 2019-2024 period showed that the Democratic Party's seat acquisition increased, from 6 seats to 7 seats and was the second most seats acquired after the Prosperous Justice Party (PKS). This study aims to describe the Recruitment Pattern of Candidates for Legislative Members of the Pekanbaru City DPRD for the 2019-2024 Period (Case Study of the Pekanbaru City Democratic Party DPC), in achieving the objectives of this study the authors used the theory of open and closed political recruitment mechanisms and the theory of the nature of Sahid Gatara's political recruitment process i.e. top-down, bottom-up and mixed. The research method used is a qualitative method by explaining descriptively. The type of research data used is primary data in the form of data obtained from research informants and secondary data obtained from related documents that can support data for research. The research location is in Pekanbaru City, Riau Province. This research suggests that the Recruitment Pattern for Candidates for Legislative Members of the Pekanbaru City DPRD for the 2019-2024 period (Case Study of the Pekanbaru City Democratic DPC) uses an open political recruitment mechanism. The Democratic Party opens opportunities for anyone who wants to register both internally and externally. As well as the political recruitment process used is mixed by combining top-down and bottom-up systems. To find the best candidate for society, the Democratic Party has 5 (five) stages in the mechanism for recruiting candidates for its legislative members. Among them are registration, psychological tests, first and second interviews, then finally determining the results. In the placement of elective areas (dapils) it is left to the candidates themselves but still under the supervision of the party. Serial numbers are determined in two ways. The first is the prerogative of the chairman of the DPC accompanied by advice and input from party officials. Second, based on the score obtained by the candidates during the selection period. The Democratic Party also assesses and considers several factors before finally determining the names that pass as candidates. Keywords: Political Recruitment, Legislative Member Candidates, DPRD